2019
DOI: 10.3390/ijerph16224489
|View full text |Cite
|
Sign up to set email alerts
|

Quadrivalent Influenza Vaccine-Induced Antibody Response and Influencing Determinants in Patients ≥ 55 Years of Age in the 2018/2019 Season

Abstract: The effects of immunization with subunit inactivated quadrivalent influenza vaccine (QIV) are not generally well assessed in the elderly Polish population. Therefore, this study evaluated vaccine-induced antibody response and its determinants. Methods: Consecutive patients ≥ 55 years old, attending a Primary Care Clinic in Gryfino, Poland, received QIV (A/Michigan/ 45/2015(H1N1)pdm09, A/Singapore/INFIMH-16-0019/2016 (H3N2), B/Colorado/06/2017, B/Phuket/ 3073/2013) between October-December 2018. Hemagglutinatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 49 publications
3
3
0
Order By: Relevance
“…Remarkably, low H1N1-specific HI responses were observed after the QIV vaccination, as also previously noted by others 26 , which limited our abilities to investigate differences in humoral H1N1-specific vaccine responses between age groups. We suggest that seasonal strain-specific effects and limited antigenic drift between vaccine strains in previous years, resulted in high pre-vaccination H1N1-specific immunity and restricted the subsequent H1N1-specific immune response to the vaccination.…”
Section: Discussionsupporting
confidence: 53%
“…Remarkably, low H1N1-specific HI responses were observed after the QIV vaccination, as also previously noted by others 26 , which limited our abilities to investigate differences in humoral H1N1-specific vaccine responses between age groups. We suggest that seasonal strain-specific effects and limited antigenic drift between vaccine strains in previous years, resulted in high pre-vaccination H1N1-specific immunity and restricted the subsequent H1N1-specific immune response to the vaccination.…”
Section: Discussionsupporting
confidence: 53%
“…Postvaccination A/Michigan/H1N1 and A/Singapore/H3N2 antibody levels were lowest and highest, respectively, in both unvaccinated and vaccinated patients. These results are in concordance with a Polish study conducted in an elderly population, 23 but zero percent in this study had been detected with prevaccination protective levels of A/Singapore/H3N2, in contrast to our results of high prevaccination Singapore serotype titers (except for the VaxigripTetra group). This discrepancy might reflect differences in circulating strains between the different countries as well as the combined effects of previous vaccinations.…”
Section: Discussionsupporting
confidence: 92%
“…Although the PR and RR for the A/H3N2 and B Yamagata lineage strains calculated in this study were similar to those previously demonstrated in individuals with obesity [ 9 , 13 ], our RRs for the A/H1N1/pdm09 and A/H3N2 strains were twice as high as those previously described for people with obesity by Neidich et al [ 8 ]. We observed higher values of MFI, PR, and RR for A/H1N1/pdm09, B Victoria lineage, and B Yamagata lineage strains and the similar values of MFI, PR, and RR for A/H3N2 strain for adults with obesity aged 60 years compared to data published by Ganczak et al from a study carried out on elderly Polish people 1 season later (2018/2019) [ 36 ]. The assessment of the QIV-induced antibody response in relation to the body composition of subjects indicated that fat mass and fat percentage were positively correlated with the magnitude of the HI antibody response to the A/H3N2 strain and the average PR, while the fat-free mass was negatively correlated.…”
Section: Discussionsupporting
confidence: 86%
“…A lower MFI (3.71) was only observed for the B Yamagata lineage strain compared to other vaccine HAs. This phenomenon can be associated with the higher pre-vaccination GMT observed for the B Yamagata lineage strain compared to those for the other 3 influenza strains [ 35 ], and was also confirmed in an elderly Polish population in a study by Ganczak et al carried out 1 season later (2018/2019) [ 36 ]. Interestingly, Bart et al observed that subjects who were seronegative at baseline demonstrated substantially higher RRs than those who were seropositive at baseline [ 35 ].…”
Section: Discussionmentioning
confidence: 76%